Study on Marine Sediment Quality Across the Coast of Kanyakumari, India: Status of Heavy Metals - Sakthykumari, I.; Vijayan, Aathira; Umayoru Bhagan, V.; Anbu, M. (Asian Journal of Chemistry, 2016)
This article gives information about the trace metal contamination along the western coast of the Kanyakumari district, Tamil Nadu, India. The results obtained from the analysis of heavy metals such as zinc, cadmium, lead, copper and iron in marine sediment samples collected during July–November 2001 are presented here. The results of chemical analysis indicate that the concentration of zinc was found to be very high at stations S11 of Mondaikkadu and S16 of Thengapattanam. The deposition of cadmium and lead in the sediment was very high at stations S6 of Kadiapattanam zone. High concentration of iron was observed at stations S4 and S17 and copper content was found to be very high at stations S7 and S10.